Effect of population breast screening on breast cancer mortality up to 2005 in England and Wales: an individual-level cohort study - Johns, Louise E; Coleman, Derek A; Swerdlow, Anthony J; Moss, Susan M (British journal of cancer, 2017)
Background: Population breast screening has been implemented in the UK for over 25 years, but the size of benefit attributable to such programmes remains controversial. We have conducted the first individual-based cohort evaluation of population breast screening in the UK, to estimate the impact of the NHS breast screening programme (NHSBSP) on breast cancer mortality. Methods: We followed 988 090 women aged 49–64 years in 1991 resident in England and Wales, who because of the staggered implementation of the NHSBSP, included both invited subjects and an uninvited control group. Individual-level breast screening histories were linked to individual-level mortality and breast cancer incidence data from national registers. Risk of death from breast cancer was investigated by incidence-based mortality analyses in relation to intention to screen and first round attendance. Overdiagnosis of breast cancer following a single screening round was also investigated. Results: Invitation to NHSBSP screening was associated with a reduction in breast cancer mortality in 1991–2005 of 21% (RR=0.79, 95% CI: 0.73–0.84, P <0·001) after adjustment for age, socioeconomic status and lead-time. Breast cancer deaths among first invitation attenders were 46% lower than among non-attenders (RR=0.54, 95% CI: 0.51–0·57, P <0.001) and 32% lower following adjustment for age, socioeconomic status and self-selection bias (RR=0.68, 95% CI: 0.63–0·73, P <0.001). There was little evidence of overdiagnosis associated with invitation to first screen. Conclusions: The results indicate a substantial, statistically significant reduction in breast cancer mortality between 1991 and 2005 associated with NHSBSP activity. This is important in public health terms.